What Lies Beneath? The Experiential Essence of Entrepreneurial Thinking - Krueger, Norris F. (Entrepreneurship Theory and Practice, 2007)
Cognitive developmental psychology and constructivism offer possibilities for the future of entrepreneurial cognition research to explore: (1) deeply seated beliefs and belief structures that ultimately anchor entrepreneurial thinking and (2) how they change as entrepreneurs move toward a more professional, expert mind–set. Such insights aid the field in identifying those developmental experiences that are the sources of those critical deep beliefs intrinsic to our mental models regarding entrepreneurship. As a field, entrepreneurship is lauded for the effectiveness of its teaching, and this essay offers strong theory to explain that our pedagogical best practices reflect important, well–known cognitive phenomena.